Action formation with janwai in Cantonese Chinese conversation - Liesenfeld, Andreas Maria (2019)
This thesis describes action formation and ascription featuring the Cantonese Chinese discourse marker janwai ("because") in naturally-occurring Cantonese talk-in-interaction. Conceived as a conversation analytic exploratory data analysis, the study examines the use of this utterance as part of the formation of turns and turn construction units in a naturalistic setting. The study is grounded in MYCanCor, a video corpus of around 20 hours of spontaneous everyday conversation that was collected as part of the study in the Malaysian Cantonese speech community. The thesis describes the use of janwai in four sequential environments, (1) the production of responses that begin with janwai, (2) the production of responses that feature janwai, (3) the production of turns and TCUs that feature janwai but that do not ostensibly constitute responses, and (4) the production of janwai in various other sequential environments, such as to format repairs and noun phrases of cause or reason in clauses. Based on the analysis of the sequential unfolding of stretches of talk-in-interaction, the thesis identifies and explicates different sets of relevance rules that appear to underpin these usage environments. This analysis presents evidence that, as part of question-response sequences, janwai can constitute an affirmative response in turn-initial position and project the forthcoming of a telling or an account either in turn-initial position or after a response token. As part of action formation, janwai appears to be related to conversational accounting and may be deployed either after a displayed intelligibility problem to preface an account or as a device to retrospectively change action formation of the preceding turn as seeking or requiring an account. These findings show that the study of grammar as an emergent, real-world phenomenon can lead to new and unexpected insights in interactional properties of causal discourse markers and thereby contribute to a better understanding of how these utterances serves as a resource that participants deploy to form turns-at-talk, negotiate social action and accomplish interactional tasks. Based on these findings, I conclude with outlining how discourse-interactional functions of janwai may be captured as part of dialogic construction grammars.